Evaluation of left atrial volume and function in systemic sclerosis patients using speckle tracking and real-time three-dimensional echocardiography - (:unkn) unknown (My University, 2016)
0

Objective: The aim of the present study was to evaluate left atrial (LA) volume and functions using real-time three-dimensional echocardiography (RT3DE) and speckle tracking in systemic sclerosis (SSc) patients.Methods: The study was designed as a cross-sectional observational study. We studied 41 consecutive SSc patients (38 females, mean age: 49.5±11.6 years) and 38 healthy controls (35 females, mean age: 48.5±10.8 years). Patients with evidence or history of cardiovascular disease and patients with risk factors as hypertension, diabetes and chronic renal failure were excluded from the study. All study subjects underwent standard echocardiography; LA speckle tracking and RT3DE was performed to assess LA volume and phasic functions. Differences between numeric variables were tested using the independent sample Student's t-test or Mann-Whitney U test, where appropriate.Results: There were no significant differences between SSC patients and controls regarding left ventricular (LV) systolic functions and twodimensional (2-D) atrial diameters. Presence of LV diastolic dysfunction (LVDD) was evaluated and graded according to recommendations of the American Society of Echocardiography. Accordingly, LVDD was observed to be significantly more frequent in SSc patients; 16 SSc patients (39%) and 5 controls (12.8%) were observed to have LVDD (p=0.007). With regard to results obtained from RT3DE, LA maximum, minimum, and before atrial contraction volumes were significantly higher (40.5±14.6 vs. 32.6±8.9, 15.5±8.4 vs. 9.9±3.5 and 28.7±11.7 vs. 21.4±7.0 mL respectively, p<0.05 for all), whereas LA active emptying fraction, LA total emptying fraction, LA expansion index, and passive emptying fraction values were significantly (47.1±12.0 vs. 52.9±10.1%, 62.8±10.5 vs. 69.5±6.7%, 187.5±76.0 vs. 246.6±96.0, 29.6±9.3 vs. 34.4±11.0% respectively, p<0.05 for all) in SSc patients than in controls. In addition, regarding results obtained from speckle tracking echocardiography, atrial peak-systolic longitudinal strain (?), early negative strain rate (SR), late negative SR, and peak positive SR values were observed to be significantly lower in SSc patients.Conclusion: LA volumes were significantly increased, and LA reservoir, conduit, and contractile functions were significantly impaired in SSc patients compared with controls. LA volume and functional analyses with RT3DE and speckle tracking may facilitate the recognition of subtle LA dysfunction in SSc patients.
Keywords: Kalp ve Kalp Damar Sistemi